Bactericidal efficacy of hydrogen peroxide on Cutibacterium acnes. Issue 1 (January 2019) - Hernandez, P.; Sager, B.; Fa, A.; Liang, T.; Lozano, C.; Khazzam, M.
Abstract : Objectives: The purpose of this study was to examine the bactericidal efficacy of hydrogen peroxide (H2 O2 ) on Cutibacterium acnes ( C. acnes ). We hypothesize that H2 O2 reduces the bacterial burden of C. acnes . Methods: The effect of H2 O2 was assessed by testing bactericidal effect, time course analysis, growth inhibition, and minimum bactericidal concentration. To assess the bactericidal effect, bacteria were treated for 30 minutes with 0%, 1%, 3%, 4%, 6%, 8%, or 10% H2 O2 in saline or water and compared with 3% topical H2 O2 solution. For time course analysis, bacteria were treated with water or saline (controls), 3% H2 O2 in water, 3% H2 O2 in saline, or 3% topical solution for 5, 10, 15, 20, and 30 minutes. Results were analyzed with a two-way analysis of variance (ANOVA) (p < 0.05). Results: Minimum inhibitory concentration of H2 O2 after 30 minutes is 1% for H2 O2 prepared in saline and water. The 3% topical solution was as effective when compared with the 1% H2 O2 prepared in saline or water. The controls of both saline and water showed no reduction of bacteria. After five minutes of exposure, all mixtures of H2 O2 reduced the percentage of live bacteria, with the topical solution being most effective (p < 0.0001). Maximum growth inhibition was achieved with topical 3% H2 O2 . Conclusion: The inexpensive and commercially available topical solution of 3% H2 O2 demonstrated superior bactericidal effect as observed in the minimum bactericidal inhibitory concentration, time course, and colony-forming unit (CFU) inhibition assays. These results support the use of topical 3% H2 O2 for five minutes before surgical skin preparation prior to shoulder surgery to achieve eradication of C. acnes for the skin. Cite this article : P. Hernandez, B. Sager, A. Fa, T. Liang, C. Lozano, M. Khazzam. Bactericidal efficacy of hydrogen peroxide on Cutibacterium acnes . Bone Joint Res 2019;8:3–10. DOI: 10.1302/2046-3758.81.BJR-2018-0145.R1.